PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) PADA BANK UMUM YANG TERMASUK DALAM SAHAM LQ45 - Eva Auria Ekananda; Jamiyla Jamiyla; Trie Sartika Pratiwi (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to determine the effect of CAR and LDR, either simultaneously or partially on ROA in the Commercial Banks included in LQ45 stocks with the observation period 2008 – 2015. The type of study is research hypothesis with purposive sampling method. The target population of this study is recorded in the Commercial Bank shares LQ45 period 2008 – 2015 announced by the Indonesian Stock Exchange. The research sample consists of 4 commercial banks. The analysis technique used is a statistical test with multiple regression method. The result showed that the CAR variable is negative effect and no significant on ROA. LDR variable is positive and significant mpact on ROA. Variables that have a dominant influence on ROA is variable LDR. And simultaneously CAR and LDR not significant effect on ROA.Key word : CAR, LDR, ROA